Passivation of Black Phosphorus via Self-Assembled Organic Monolayers by van der Waals Epitaxy - Zhao, Yinghe (Advanced materials (Deerfield Beach, Fla.), 2017)
© 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.